THE COHESIVE DEVICES USED IN THE CAUSE EFFECT ESSAY WRITTEN BY THE ENGLISH DEPARTMENT STUDENTS OF STKIP ST. PAULUS RUTENG - Stanislaus Guna; Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2015)
The purpose of this research study is to analyze the types of cohesive devices, the frequency of each cohesive device used and to identify cohesive errors that the students committed in their cause - effect essay. There were 29 students’ essays analyzed.. The study revealed that there were four types of cohesive devices used by the students in their essay: Reference, Substitution, Conjunction and Lexical cohesion. In accordance with the frequency of cohesive device, reference had the highest frequency which is 45,38%, followed by Lexical Cohesion 39,33%, Conjunction 14,90%, and Substitution 0,37%. The types of reference: personal, demonstrative and comparative rerference; types of substitution is nominal substitution; types of conjunction: additive, adversative, causal and temporal conjunction, and lexical cohesion: reiteration (repetition, synonym, general word and antonym) and collocation (adjectives + nouns, noun + noun, and verb + preposition) . Dealing with the errors in cohesive devices, the most frequency of errors was reference with the percentage 55,85%, conjunction 16,48%, lexical cohesion 2,76%. The research study revealed that most of the students committed errors in accordance with the source of interlanguage errors and intralingual errors. Most of the students committed errors on pronoun shift refers to grammatical errors, misuse of plural and singular form of demonstrative pronoun, overuse of cohesive devices, run-on sentence, misuse of cohesive devices and overgeneralization in their cause effect essay. The results of this study can contribute some pedagogical implications for writing teachers and students. It is necessary for English teacher to teach cohesion and cohesive devices explicitly and provide them with ample examples in English classes.